DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON LOCAL WISDOM OF JAMBI ORIENTED BY STUDENTS' CREATIVE THINKING ABILITY IN HIGH SCHOOL PHYSICS SUBJECTS - Anto, Yulianto; Zurweni, Zurweni; Harjono, Hary Soedarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research is development research in the form of interactive multimedia based on Jambi local wisdom. This research aims to develop interactive multimedia based on Jambi local wisdom which is oriented towards students' creative thinking abilities in learning physics in high school, using the Lee and Owen Method. This method integrates the principles of instructional design, action research, and innovative approaches to produce a multimedia product that is effective in improving student understanding and skills. The initial stage of research involves analyzing student needs and identifying creative thinking abilities relevant to physics material. Then, action research was carried out to understand the dynamics of physics learning in high school and design appropriate multimedia. The multimedia development process was carried out iteratively, involving media and material expert validators, feedback from teachers and field tests on grade 10 high school students. Multimedia implementation is carried out in the context of classroom physics learning, where its effectiveness is evaluated through questionnaires and interviews with teachers and students. The evaluation results are used to improve and enhance multimedia so that it is more responsive to student learning needs. It is hoped that this research can contribute to the development of learning models that combine local wisdom with innovative approaches in teaching physics in high schools, as well as improving students' creative thinking abilities through the use of multimedia technology.